2011
DOI: 10.5114/pwki.2011.21188
|View full text |Cite
|
Sign up to set email alerts
|

Association on cardiovascular interventions of PCS Current status of drug-eluting stents and drug-eluting balloons in patients with stable coronary artery disease: An expert consensus document of the Association for Percutaneous Cardiovascular Interventions and Polish Cardiac Society

Abstract: S t r e s z c z e n i ePomimo istotnego zmniejszania częstości restenozy i ponownych zabiegów rewaskularyzacyjnych przez stenty uwalniające leki antyproliferacyjne (ang. drug eluting stents -DES), istnieją sprzeczne dane na temat podwyższonego ryzyka występowania późnej zakrzepicy w DES w porównaniu ze stentami metalowymi (ang. bare metal stent -BMS). Z pewnością wynika to z różnej skuteczności i bezpieczeństwa poszczególnych rodzajów DES, których liczba systematycznie się zwiększa. Ponadto w ostatnim okresie … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 119 publications
(149 reference statements)
0
3
0
Order By: Relevance
“…Though it has been reported that atorvastatin concentration as low as 0.1 μM was effective in suppressing the growth of smooth muscle cells, , controlled release of atorvastatin to provide such low concentration has not been demonstrated. Considering that the drug loading in current stents commonly is 100 μg/cm 2 or greater, the capability to effectively deliver drug using much lower loading is expected to contribute to minimizing system toxicity while inhibiting HCASMC growth. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though it has been reported that atorvastatin concentration as low as 0.1 μM was effective in suppressing the growth of smooth muscle cells, , controlled release of atorvastatin to provide such low concentration has not been demonstrated. Considering that the drug loading in current stents commonly is 100 μg/cm 2 or greater, the capability to effectively deliver drug using much lower loading is expected to contribute to minimizing system toxicity while inhibiting HCASMC growth. , …”
Section: Resultsmentioning
confidence: 99%
“…Considering that the drug loading in current stents commonly is 100 μg/cm 2 or greater, 6 the capability to effectively deliver drug using much lower loading is expected to contribute to minimizing system toxicity while inhibiting HCASMC growth. 59,60 Overall, the combination of nanocoating surface and drug release substantially reduced the viability and proliferation of HCASMC on PDE31 coated atorvastatin. For example, at 10 μg/cm 2 , the MTT and BrdU activities of HCASMC were suppressed to 56.7% and 55.6% of the control, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Similar recommendations for DES use in STEMI (class IIa, earlier IIb) are present in the guidelines of the American cardiology societies [ 41 ]. Experts of the Polish Society of Cardiology do not preclude the use of DES, whose efficacy is proved in a selected population of STEMI patients [ 42 ].…”
Section: Discussionmentioning
confidence: 99%